Research on the Temperature Field and Frost Heaving Law of Massive Freezing Engineering in Coastal Strata - Chaochao Zhang; Dongwei Li; Junhao Chen; Guanren Chen; Chang Yuan; Zecheng Wang; Guosheng Ding; Xin Chen; Minghai Xia; Shengfu Wang; Bo Zhang; Ru He; et al. (Advances in Materials Science and Engineering)
In this study, based on the background of massive freezing engineering in coastal strata, the thermal physical parameters and some freezing laws of soil were obtained through soil thermal physical tests and frozen soil frost heaving tests. When the freezing temperatures were −5°C, −10°C, −15°C, and −20°C, the frost heaving rates of the soil were 0.53%, 0.95%, 1.28%, and 1.41%, and the frost heaving forces of the soil were 0.37 MPa, 0.46 MPa, 0.59 MPa, and 0.74 MPa, respectively. In the range of test conditions, the frost heaving rate and the frost heaving force of the soil increased with the decrease of the freezing temperature, and the relationship was roughly linear with the temperature. The entire cooling process could be roughly divided into three stages: active freezing stage, attenuation cooling stage, and stability stage. The range of the frozen soil expansion did not increase linearly with the decrease of the freezing temperature, and there was a limit radius for the frozen soil expansion. A three-dimensional finite element model was established to simulate the temperature field and frost heaving of the soil under the on-site working conditions. The entire frost heaving process could be roughly divided into two stages. The calculated temperature values and the frost heaving force values were compared with the on-site measured values, and the results verified that the numerical calculation could accurately reflect the temperature field and frost heaving law of the formation.